Investigation on picosecond laser-induced damage in HfO2/SiO2 high-reflective coatings. (October 2018) - Li, Cheng; Zhao, Yuan'an; Cui, Yun; Wang, Yueliang; Peng, Xiaocong; Shan, Chong; Zhu, Meiping; Wang, Jianguo; Shao, Jianda
Highlights: 4L layer can slightly improve the LIDT of HR coatings tested by 30-ps, 1064 nm pulses. The damages of two coatings (with and without 4L layer) were E-field-dependent. Damage morphologies were similar to those tested by 355-nm nanosecond pulses. Abstract: We investigate the influence of a protective layer on the picosecond laser-induced damage in HfO2 /SiO2 high-reflective (HR) coatings. Two types of 1064-nm HR coatings, with and without a SiO2 protective layer, are deposited using electron beam evaporation. Laser-induced damage tests are operated with 1064-nm, 30-ps laser pulses in one-on-one mode. Five different angles of incidence (AOIs) are considered in the tests for both coatings, in order to modulate the electric field ( E -field) intensity in the HR coatings. The damage morphologies and cross-sections of the damage sites are characterized using scanning electron microscope (SEM) and focused ion beam (FIB), respectively. Experimental results show that the SiO2 protective layer slightly improves the laser-induced damage threshold (LIDT) of the HR coatings for all AOI values. The damage morphology contains high-density micrometer-scale pits and layer delaminations, at low and high fluences, respectively. The cross-sections of the damage sites and LIDTs for different AOIs are compared with corresponding E -field distributions. For both coatings, the damage is initiated near the peak of the E -field. A negative linear relationship is observed between the LIDT and corresponding maximum E -field intensity for both coatings.